Geophysical data acquisition education for high school students through field observation - Muhardi, Muhardi; Putra, Yoga Satria; Perdhana, Radhitya; Jumarang, Muh Ishak; Sampurno, Joko; Muliadi, Muliadi; Ihwan, Andi; Adriat, Riza; Zulfian, Zulfian; Sutanto, Yuris; Faryuni, Irfana Diah (Community Empowerment, 2025)
Most high school students in Singkawang City and Bengkayang Regency still require a more comprehensive understanding regarding the application of geophysics, which can impact their skills in conducting field observations. This Community Service (PkM) aims to enhance students' skills in geophysical data acquisition through field observations at Karta Beach, Bengkayang Regency. The activity was carried out in three stages: preparation, implementation, and evaluation. During the implementation stage, participants were educated about geophysical data acquisition through field observations, including geoelectric, self-potential, meteorology, and geology practicums. Based on the evaluation results, a score of 87.31 (very good) was obtained, indicating an increase in students' skills in geophysical data acquisition through field observations.